Bio-efficacy and phytotoxicity of pre-emergence herbicide mixtures on weed growth and yield in transplanted rice (Oryza sativa L.) - Narayan prasad kafle, Shrijan kafle; Manoj Kumar Singh; Dendukuri Udaya Lakshmi; Virendra Choudhary (The Indian Journal of Agricultural Sciences, 2026)
Weeds are the major factor reducing grain yield in transplanted rice. A comprehensive study about the bio-efficacy and phytotoxicity of pre-emergence herbicide mixtures on weed growth and yield in transplanted rice (Oryza sativa L.) was conducted during the Kharif season of 2023 at Agricultural Research Farm, Banaras Hindu University, Varanasi, the study aimed to assess the impact of various pre-emergence herbicide mixtures on weed control, rice yield, phytotoxicity and economic analysis. The experiment was laid out in randomized complete block design in field with 9 herbicide treatments including control. The treatments having herbicide mixtures consist of metsulfuron methyl 0.02% + chlorimuron ethyl 0.02% + pretilachlor 7.54 % GR having doses @ 452.4, 603.2, 754.0 (recommended), 942.5 and 1508 (double) g a.i. ha-1, pretilachlor 30% + pyrazosulfuron ethyl 0.75% WDG @ 615 g.a.i. ha-1, bensulfuron methyl 0.6% + pretilachlor 6% GR @ 660 g.a.i. ha-1 and oxidiazon + pretilachlor @ (520 + 150) ml a.i. ha-1. Key findings of study revealed that the herbicide combination of oxidiazon + pretilachlor @ (520 + 150) ml a.i. ha-1 significantly reduced weed density, weed dry weight, demonstrating superior weed control efficiency with highest rice grain yield compared to other pre-emergence herbicide mixtures, despite causing notable phytotoxicity symptoms in rice. It was at par with metsulfuron methyl + chlorimuron ethyl + pretilachlor @ 1508 g a.i. ha-1 (double) and metsulfuron methyl + chlorimuron ethyl + pretilachlor @ 754 g a.i. ha-1 (recommended). However, economic analysis indicated that oxidiazon + pretilachlor @ (520 + 150 ml a.i. ha-1) provided the highest net return and benefit-cost ratio, making it economically an effective option.  The study highlights the need of pre-emergence herbicides mixtures to optimize both weed control and productivity in transplanted rice.